The Important Role of Intellectual Capital for SME (Small Medium Enterprise) - Ilahiyah, Mar’a Elthaf (Opción, 2019)
The purpose of this research is to know the importance of the role and application of intellectual capital against informal business units. Approach to the research methods used in this research is qualitative case study applied in the Small Medium Enterprise in developing countries, such as Indonesia. In result, when a leadership style that was applied by a leader is different from the person who is led, then there will be a decrease in the productivity of work. It was concluded that the intellectual capital that is measured using the leadership, employee competencies, and loyalty/commitment has not optimized properly.